PP14 Exploitation of copoazú (Theobroma grandiflorum) seed husk: Evaluation of bioactive compounds and antioxidant activity - Paladines Beltrán, Gloria; Venegas Morales, Nathalia Alejandra; Vargas Rocha, Valentina (Revista Productos Naturales, 2025)
Cupuaçu (Theobroma grandiflorum) is a valuable Amazonian fruit, whose seeds generate by-products such as the husk, which are often underutilized [1,2]. Given its nutritional potential and similarity to cocoa husk [3], this study evaluated the extraction of bioactive compounds from cupuaçu seed husk using ultrasound-assisted extraction (UAE) and conventional extraction (CE). UAE with 70% ethanol for 75–120 minutes improved the recovery of nutritional compounds, phenolics, flavonoids, and antioxidant activity compared to CE, which required 96 hours [4]. These findings highlight the efficiency of UAE for valorizing agro-industrial residues.